2022
DOI: 10.3390/su14042341
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Machine Learning Models in Predicting Irrigation Groundwater Quality Indices for Effective Decision Making in Medjerda River Basin, Tunisia

Abstract: Over the last years, the global application of machine learning (ML) models in groundwater quality studies has proved to be a robust alternative tool to produce highly accurate results at a low cost. This research aims to evaluate the ability of machine learning (ML) models to predict the quality of groundwater for irrigation purposes in the downstream Medjerda river basin (DMB) in Tunisia. The random forest (RF), support vector regression (SVR), artificial neural networks (ANN), and adaptive boosting (AdaBoos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…The RF model, developed by Breiman (2001), is based on an ensemble of decision trees with controlled variance. The RF model has been widely used for regression and classi cation problems Such as land use/cover mapping (Magidi et al, 2021) and water quality eld (Kouadri et al, 2021;Trabelsi and Bel Hadj Ali, 2022). The detailed data and computation procedure of the RF model can be found in (Breiman, 2001; Ferreira and da Cunha, 2020a).…”
Section: Random Forest (Rf)mentioning
confidence: 99%
“…The RF model, developed by Breiman (2001), is based on an ensemble of decision trees with controlled variance. The RF model has been widely used for regression and classi cation problems Such as land use/cover mapping (Magidi et al, 2021) and water quality eld (Kouadri et al, 2021;Trabelsi and Bel Hadj Ali, 2022). The detailed data and computation procedure of the RF model can be found in (Breiman, 2001; Ferreira and da Cunha, 2020a).…”
Section: Random Forest (Rf)mentioning
confidence: 99%
“…This may be related to the significant correlation between the input and output variables (Mokhtar et al 2022). The more significant the correlation between the input and output variables, the higher the performance of the models (Trabelsi and Ali 2022). El Bilali (2021) reported that ANN models are less sensitive to input variables.…”
Section: Comparison Of Ann and Anfis Modelsmentioning
confidence: 99%
“…At Level 1, the indices were normalized from 0 to 1, to minimize the effect of scale. The GWQI indexes were normalized by Equation (10), while the GQI index was normalized by Equation (11).…”
Section: Level 1: Data Fusionmentioning
confidence: 99%